Evaluasi Nilai Setting Rele Jarak Sebagai Proteksi Saluran Udara Tegangan Tinggi 150 KV Menggunakan DigSilent Power Factor - Hajar, Ibnu; Shodik, Muhammad Jafar (SUTET, 2024)
The electric power system is a complex system, it needs to be maintained so the system can run optimally. Many factors can interference the transmission and distribution system process from sources (power plant) to consumers. In order to maintain the reliability and security of the transmission line, a protection system is needed. The protection system must work in its working area and not overlaping each other. The protection system that commonly used to secure the transmission line is distance relay. The working principle of the distance relay is sensing the impedance and dividing the impedance into several zones so the relay can works simultinously with other relays. This study uses a quantitative method to collect data, simulate them, and compare the relay setting result with IEEE Standard. In this case, the result of the calculation of the zone impedance value in zone-1 is 2.562 ohms, zone-2 is 4.611 ohms and zone-3 is 7.852 ohms. The simulation results show that these settings correspond with the IEEE C37.113.2015 standard and work selectively in their respective zones.